Time for Physical Activity: Different, Unequal, Gendered. (March 2022) - Doan, Tinh; Yu, Peng; LaBond, Christine; Gong, Cathy; Strazdins, Lyndall
We investigate time inequity as an explanatory mechanism for gendered physical activity disparity. Our mixed-effect generalized linear model with two-stage residual inclusion framework uses longitudinal data, capturing differing exchanges and trade-offs in time resources. The first stage estimates within-household exchanges of paid and family work hours. Estimates show that men's employment increases women's family work hours while reducing their own, whereas women's employment weakly affects men's family time. Incorporating unequal household exchange into the second stage reveals that as women's paid or family work hours increase, physical activity goes down. In contrast, men's physical activity is unaffected by paid work hours, and family time appears protective. Control over work time further underscores gendered time exchange: Men's activity increases with own or partner's control, whereas women's increases only with their own. Our approach reveals how men's and women's unequal capability to use time creates differing trade-offs between work, family, and physical activity, generating health inequity.